Systémy chlazení elektromobilu - Šimáček, Daniel (Vysoké učení technické v Brně. Fakulta strojního inženýrství, 2022)
Tato rešeršní bakalářská práce se zabývá problematikou systémů chlazení elektromobilů. První část se věnuje teoretickému popisu komponent produkující největší část tepla – baterie a elektromotor. Zmíněna je i teorie přenosu a prostupu tepla za účelem lepší návaznosti problematiky chlazení. Druhá část je věnována popisu aktuálních přístupů chlazení komponent elektromobilu – baterie a elektromotoru. V části o chlazení elektromotoru je srovnání přístupů chlazení se spalovacím motorem. Dále jsou popsány alternativní způsoby chlazení.

This bachelor thesis deals with the issue of cooling systems for electric vehicles. The first part is devoted to the theoretical description of the components producing the largest part of the heat - the battery and the electric motor. Heat transfer theory is also mentioned to better relate the cooling issues. The second part focuses on the description of the current cooling approaches for the electric vehicle components - battery and electric motor. The section on electric motor cooling includes a comparison of cooling approaches with the internal combustion engine. Alternative cooling methods are described in next section.
Cooling systems of battery vehicle
Keywords: chlazení; teplo; baterie; elektromotor; výměník; cooling system; heat; battery; electric motor; heat exchanger